ANALISIS JUAL BELI PAKET DATA INTERNET DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Syukron Abdi, Abdi (EKSYDA: Jurnal Studi Ekonomi Syariah, 2024)
The purpose of this research was carried out in order to fulfill the assignment for the Multiple Intelligence course. This research aims to determine the buying and selling of internet data packages according to an Islamic economic perspective. The type of research used in this research is field research with qualitative descriptive research methods. Meaningful research is to create a picture of the facts, characteristics and relationships between the phenomena being investigated, with this the author aims to describe how internet data packages are bought and sold using data collection such as interviews, observation and documentation. And the place for research here is at the East Lampung Azka Cell Counter. The results of this research can be concluded that the law of buying and selling internet data package cards is based on Sayyid Sabiq’s perspective, that goods being bought and sold must know their condition, type (quantity and quality) and price. If one of them is unknown, the sale and purchase will be invalid and void because there is an element of uncertainty or ambiguity (gahrar).